Transjugular Intrahepatic Portosystemic Shunt (TIPS) - Tanisaro, Komgrit; Suchato, Chirotchana; Varatorn, Rergchai (The Bangkok Medical Journal, 2013)
Surgery for portal hypertension began in 1877, with Nicolai Vladirmirovich who performed the À rst portacaval anastomosis. There was little clinical success until Blakemore and Whipple between the 1920’s and 1940’s: the mortality rate ranged from 25-40%. Hepatic encephalopathy was a clinical problem. In 1960, Warren and collegues performed a distal splenorenal shunt, which reduced the incidence of hepatic encephalopathy to an acceptable level.1 Other complications after undergoing successful portacaval anastomosis included ammonia toxicity, responsible for the neuropsychiatric changers seen in patients with impending hepatic coma2 and progressive hypersplenism, inducing thrombocytopenia and leucopenia which can become life-threatening after a shunt procedure.3 Transjugular intrahepatic portosystemic shunt (TIPS) is a less invasive, non-surgical procedure basis which minimizes complications in the treatment of portal hypertension.4 The procedure is mostly performed by Interventional Radiologists (IR) and is effective in selected cases of cirrhosis and portal hypertension.